(untitled) (FULafia Journal of Science and Technology, 2023)
Laccase (EC.1.10.3.2. Diphenol oxidase) are multicopper oxidases that catalyze oxidation of many substituted phenolic compounds, aromatic amines including some inorganic substances by using molecular oxygen as electron acceptor. Nevertheless, most laccases that have been studied so far are not well-suited for industrial applications due to their low stability at high temperatures or pH values. This research focused on identifying and characterizing novel fungal laccases that have potential for industrial applications as well as developing efficient production methods for laccases. Lenzite elegans, a white rot fungi was screened by plate tests using indicator compound 2,2’ Azinobis(3-thylbenzthiazoline-6-sulfonic ) acid (ABTS). The ability of Lenzite elegans to produce laccase was studied in liquid media. This fungal species produced significant amounts of laccase in titers (958 U), and the enzyme was preliminarily characterized. The novel laccase was found to be rather typical basidiomycete laccase.